Assessing whether medical language is a barrier to receiving healthcare services in Bangladesh: an exploratory study. Issue 2 (2019) - Bhuiyan, Badrul Alam; Urmi, Ishrat Jahan; Chowdhury, Mahbub Elahi; Rahman, Tajrian; Hasan, Abu Syed; Simkhada, Padam
No abstract available